Circulating KRAS G12D but not G12V is associated with survival in metastatic pancreatic ductal adenocarcinoma - Till, Jacob E.; McDaniel, Lee; Chang, Changgee; Long, Qi; Pfeiffer, Shannon M.; Lyman, Jaclyn P.; Padrón, Lacey J.; Maurer, Deena M.; Yu, Jia Xin; Spencer, Christine N.; Gherardini, Pier Federico; Da Silva, Diane M.; et al. (Nature communications, 2024)
While high circulating tumor DNA (ctDNA) levels are associated with poor survival for multiple cancers, variant-specific differences in the association of ctDNA levels and survival have not been examined. Here we investigate KRAS ctDNA (ctKRAS) variant-specific associations with overall and progression-free survival (OS/PFS) in first-line metastatic pancreatic ductal adenocarcinoma (mPDAC) for patients receiving chemoimmunotherapy (“PRINCE”, NCT03214250), and an independent cohort receiving standard of care (SOC) chemotherapy. For PRINCE, higher baseline plasma levels are associated with worse OS for ctKRAS G12D (log-rank p = 0.0010) but not G12V (p = 0.7101), even with adjustment for clinical covariates. Early, on-therapy clearance of G12D (p = 0.0002), but not G12V (p = 0.4058), strongly associates with OS for PRINCE. Similar results are obtained for the SOC cohort, and for PFS in both cohorts. These results suggest ctKRAS G12D but not G12V as a promising prognostic biomarker for mPDAC and that G12D clearance could also serve as an early biomarker of response. ctDNA is a known poor prognostic factor for multiple cancer types, but variant-specificity is unknown. Here, the authors show variant-specific association of ctKRAS levels with survival in previously untreated metastatic pancreatic ductal adenocarcinoma patients in multiple cohorts.